2022
DOI: 10.3390/jcm11123498
|View full text |Cite
|
Sign up to set email alerts
|

Early Structural and Vascular Changes after Within-24 Hours Vitrectomy for Recent Onset Rhegmatogenous Retinal Detachment Treatment: A Pilot Study Comparing Bisected Macula and Not Bisected Macula

Abstract: Background: In this study we aimed at investigating macular perfusion/anatomical changes in eyes with early onset rhegmatogenous retinal detachment (RRD) after prompt surgery within 24 hours, comparing a bisected macula and not bisected macula RRD. Methods: In this prospective observational study, 14 eyes of 14 patients who underwent within-24 hours vitreoretinal surgery for early onset RRD were enrolled. Patients were further divided into two subgroups: the not bisected macula group (NBM group) and the bisect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Twelve studies including 430 RRD eyes and 430 control eyes were selected in this study ( Agarwal et al, 2019 ; Woo et al, 2018 ; McKay et al, 2020 ; Ng et al, 2020 ; Wang et al, 2019 ; Hong et al, 2020 ; Bonfiglio et al, 2020 ; Barca et al, 2020 ; Christou et al, 2021 ; Liu et al, 2021 ; D'Aloisio et al, 2022 ; Chatziralli et al, 2022 ), as indicated in Table 1 . The search strategy for Pubmed is showed in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies including 430 RRD eyes and 430 control eyes were selected in this study ( Agarwal et al, 2019 ; Woo et al, 2018 ; McKay et al, 2020 ; Ng et al, 2020 ; Wang et al, 2019 ; Hong et al, 2020 ; Bonfiglio et al, 2020 ; Barca et al, 2020 ; Christou et al, 2021 ; Liu et al, 2021 ; D'Aloisio et al, 2022 ; Chatziralli et al, 2022 ), as indicated in Table 1 . The search strategy for Pubmed is showed in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…As showed in Table 1 , two studies selected macular-on RRD, six studies collected macula-off RRD, and the remaining four studies included both macula-on and macula-off RRD. In the study by D'Aloisio et al, part of the macula was detached before surgery in 6 RRD patients who received treatment within 24 h of onset ( D'Aloisio et al, 2022 ). This group of eyes was considered as macular-on RRD for analysis in our study.…”
Section: Resultsmentioning
confidence: 99%
“…A fair number of studies with a follow-up no longer than 8 months were investigated. Reduction of VD in retinal capillary plexuses in comparison to fellow eyes at post-operative follow-up was usually reported in literature, with more significant evidence in Macula-OFF condition [ 11 , 21 , 22 , 23 , 24 , 25 ]. In contrast, Hong et al found that the SCP and DCP VD in the operated eyes did not differ significantly from the fellow eyes for both the Macula-ON and Macula-OFF groups, at 6 months follow-up [ 26 ].…”
Section: Discussionmentioning
confidence: 75%
“…Diabetic retinopathy (DR) is associated with systemic vascular complications likely reflecting widespread microvascular disease, and OCTA has become the tool of choice for the early detection of DR and other retinal vascular diseases [ 15 , 20 , 21 , 22 , 23 , 24 ]. Recent studies have demonstrated that retinal vessel density and retinal perfusion reflect systemic inflammatory responses [ 22 , 25 , 26 ] and that retinal and choroidal thickness may serve as potential biomarkers of systemic inflammation [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%